California Adult Education Handbook - Bauer, Thomas J.; California State Dept. of Education, Sacramento. Adult, Alternative, and Continuation Education Div. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
This handbook provides descriptions of standard practices in adult education administration as well as the policies, regulations, and statutes guiding the practices. It is a useful resource in day-to-day decision making in program administration or a basic guide for adult education program development. Section 000 provides the general requisites of adult education in regard to separate adult schools; adult classes maintained in conjunction with other schools/centers; administrative regulations; classes for adults in county jails, industrial farms, and road camps; and attendance. Section 100 on program and course approval covers criteria for approval of apportionment courses and course outlines. Section 200 presents the general requirements for adult programs in parenting and elementary and secondary basic skills, English as a second language, citizenship, handicapped program, short-term vocational programs with high employment potential, programs in home economics, health and safety, programs for older adults, federal Adult Basic Education Act, nursing homes and convalescent hospitals, classes for handicapped adults, community service classes, and apprenticeship program. Section 300 on personnel administration provides requirements for teacher employment and leave of absence. Section 400 on budget and adult education finance offers guidelines for adult education income and defines budget, accounting, and other terminology. An index is attached. (YLB)
Availability: Publications Sales, California Dept. of Education, P.O. Box 271, Sacramento, CA 95802-0271 ($4.00).
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Education; Adult Programs; Adult Vocational Education; Courses; Educational Administration; Educational Finance; Guidelines; Personnel Management; Program Administration; Program Development; Program Implementation; Program Validation; Standards; Guides, Non-Classroom.